Analysis of clinical and biochemical characteristics and left ventricular hypertrophy in patients with indeterminate saline infusion test results - Qu, Huiyun; Zhao, Jingge; Wang, Lulu; Du, Huiyu; Zhang, Qinghui; Sun, Tingxi; Zhang, Chen; Chen, Jiaxuan; Guo, Linya; Huang, Qi; Tian, Dandan; Liu, Zhilan; et al. (Frontiers in Endocrinology, 2024)
Introduction: The clinical biochemical characteristics and target organ damage (TOD) in patients with plasma aldosterone concentrations (PAC) ranging from 50 to 100 ng/L after a saline infusion test (SIT) have not been fully studied. Methods: A total of 611 hypertensive patients with an elevated aldosterone-to-renin ratio (ARR) who underwent a supine SIT at Henan Provincial People's Hospital were enrolled. The patients were divided into three groups according to their post-SIT PAC: <50 ng/L (control group), 50–100 ng/L (indeterminate post-SIT results group), and >100 ng/L (PA group). The clinical and biochemical characteristics and TOD of the three groups were compared. The correlation of the post-SIT PAC with left ventricular mass index (LVMI) was assessed via regression analysis. Results: The indeterminate post-SIT results group had the youngest patients and the shortest duration of hypertension. The prevalence of renal impairment (RI) and left ventricular hypertrophy (LVH) was lower than that in the PA group (P<0.05), but there was no statistically significant difference from the control group (P>0.05). After adjustment for confounders, the risk of developing carotid plaque was greater in the indeterminate post-SIT results group than in the control group (OR 1.73, 95% CI: 1.11, 2.69), and the prevalence of RI and LVH tended to increase with increasing post-SIT PAC levels. In multiple regression analyses, LVMI was significantly correlated with post-SIT PAC (P<0.05), but the basal PAC, plasma renin activity, and ARR did not significantly correlate with LVMI (P>0.05). Conclusion: A post-SIT PAC of 50–100 ng/L may be indicative of an early form of PA, and it may serve as an independent predictor of LVH, which could be related to the level of autonomously secreted aldosterone.